Sustainable Development and the Islamic Vision of Development: A Comparative Analytical Study (The International Journal of Educational Sciences and Arts, 2025)
This study aims to provide an in-depth analytical comparison between the United Nations Sustainable Development Goals and the developmental principles within Islamic Sharia law, employing a rigorous scientific methodology based on comparative analysis and constructive critique. The contemporary academic arena witnesses growing interest in examining the intersections and divergences between global developmental models and local civilizational frameworks, particularly amid escalating debates concerning the effectiveness of Western developmental models within diverse cultural contexts. The Sustainable Development Goals adopted by the United Nations in 2015 represent one of the most prominent global developmental models that seek to achieve equilibrium between economic growth, social justice, and environmental sustainability. Conversely, Islamic Sharia law presents a comprehensive developmental framework grounded in established principles and values aimed at achieving human prosperity in both this world and the hereafter. The study's findings reveal significant intersections between the two models in the domains of social justice, environmental preservation, and human development, while demonstrating fundamental differences in philosophical, ethical, and epistemological foundations, particularly regarding issues of gender identity and moral values. The study concludes that mutual cooperation between the two models is feasible, with the imperative of respecting the religious specificities and moral values of states within this framework. Furthermore, the study proposes the development of an integrated theoretical framework for sustainable development from an Islamic perspective that combines moral values with addressing contemporary issues.
Keywords: Sustainable Development; Sustainable Development Goals; Islamic Development Vision, Maqasid Al-Shariah; Comparative Analysis; Gender Identity